Effect of minor Nb substitution for Co on the glass forming ability and magnetic properties of the Gd50Co50 metallic glass. (22nd May 2019) - Zhang, Z; Cheng, H; Ding, D; Zhang, H Y; Chen, S S; Xia, L; Li, W H
Abstract: In the current work, slight amount of non-magnetic Nb element was added in the Gd50 Co50 binary alloy as a substitution of transition metal Co and Gd50 Co50− x Nb x ( x  = 2, 5) metallic glasses were obtained using a melt-spinning method. Glass-forming ability (GFA) and magnetic performances of the metallic glasses were measured and compared to those of the Gd50 Co50 binary metallic glass. The effect of Nb replacement on the GFA, Curie temperature and magneto-caloric effect of the Gd50 Co50− x Nb x metallic glasses, as well as the related mechanism, were investigated.